PW 2149 Issues in data availability and results in two international surveys on drowning. (November 2018) - Salmi, Louis-Rachid; Tellier, Eric; Simonnet, Bruno
Abstract : Context and objective: Documentation of country-specific burden of injuries is needed to target circumstances, to develop countermeasures, and to set baselines to assess their impact. For drowning, two sources are used in international comparisons, the Global Burden of Disease (GBD) study, and the World Health Organization (WHO) global health estimates. Ideally, such sources should cover all countries and provide reliable information. Our objective was to describe the availability of country-specific data on drowning and to assess the agreement between GBD and WHO surveys. Methods: We used the World Bank database on Countries and Economies and country Internet sites to collect population data on all countries as of 2016. Drowning death rates per 1 00 000 were computed from GBD and WHO reports. We classified countries by region and income level, from their Gross National Income (Atlas Method). Proportions and characteristics of countries participating to either or neither studies were described. For countries participating to both studies, agreement of drowning mortality estimates was judged on the intra-class coefficient (ICC) and Bland and Altman graph. Results: Of 226 countries, 113 participated to WHO and 183 to GBD. Compared to all countries, 89 participants to GBD only were mostly from Africa (56.2% vs 24.8%), of low- or low-middle income countries (79.8% vs 38.5%), and had a larger population (mean 56.9 M vs 32.8 M). Participants to WHO only were mostly small non-independent Caribbean countries (73.7% vs 12.4%). Non-participants to either study were mostly small states from Oceania or Europe (mean population: 55, 000). Among 94 participants to both studies, the agreement between estimates was excellent (ICC=0.988); WHO, however, was on average lower than GBD (−2.2/100, 000; range −9.9 to 8.4). Conclusion: The burden of drowning in missing countries is probably low, but reasons for non-participation and discrepancies between sources, including the need for capacity building, should be analyzed.